Technology for Advanced Focal Plane Arrays of HgCdTe and AlGaN - He, Li; Yang, Dingjiang; Ni, Guoqiang (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book introduces the basic framework of advanced focal plane technology based on the third-generation infrared focal plane concept. The essential concept, research advances, and future trends in advanced sensor arrays are comprehensively reviewed. Moreover, the book summarizes recent research advances in HgCdTe/AlGaN detectors for the infrared/ultraviolet waveband, with a particular focus on the numerical method of detector design, material epitaxial growth and processing, as well as Complementary Metal-Oxide-Semiconductor Transistor readout circuits. The book offers a unique resource for all graduate students and researchers interested in the technologies of focal plane arrays or electro-optical imaging sensors.